10-year results of a new low-monomer cement: Follow-up of a randomized RSA study - Söderlund, Per (Informa Healthcare, 2012)
BACKGROUND AND PURPOSE: The properties and performance of a new low-monomer cement were examined in this prospective randomized, controlled RSA study. 5-year data have already been published, showing no statistically significant differences compared to controls. In the present paper we present the 10-year results. METHODS: 44 patients were originally randomized to receive total hip replacement with a Lubinus SPII titanium-aluminum-vanadium stem cemented either with the new Cemex Rx bone cement or with control bone cement, Palacos R. Patients were examined using RSA, Harris hip score, and conventional radiographs. RESULTS: At 10 years, 33 hips could be evaluated clinically and 30 hips could be evaluated with RSA (16 Cemex and 14 Palacos). 9 patients had died and 4 patients were too old or infirm to be investigated. Except for 1 hip that was revised for infection after less than 5 years, no further hips were revised before the 10-year follow-up. There were no statistically significant clinical differences between the groups. The Cemex cement had magnitudes of migration similar to or sometimes lower than those of Palacos cement. In both groups, most hips showed extensive radiolucent lines, probably due to the use of titanium alloy stems. INTERPRETATION: At 10 years, the Cemex bone cement tested performed just as well as the control (Palacos bone cement).